Analysis of the effects of Bacillus velezensis HJ-16 inoculation on tobacco leaves based on multi-omics methods - Zhou, Qing; Yang, Jinchu; Feng, Yingjie; Yang, Zongcan; Wang, Yixuan; Zhang, Zhan; Zhang, Tingting; Liu, Wenzhao; Xu, YongMing; Yang, Yongfeng; Huang, Jihong (Frontiers in Bioengineering and Biotechnology, 2024)
In this study, a strain isolated from the surface of flue-cured tobacco leaves, identified as Bacillus velezensis HJ-16, was applied in the solid-state fermentation of tobacco leaves. This strain, known for producing thermally stable enzymes, including amylase, cellulase, and protease, significantly improved the sensory qualities of tobacco, enhancing aromatic intensity, density, and softness, while reducing irritation. Whole-genome sequencing and functional annotation revealed that B. velezensis HJ-16 possesses a single circular chromosome containing genes associated with enzyme production and metabolic activities, particularly in carbohydrate metabolism and amino acid metabolism. Untargeted metabolomics analysis identified significant changes in non-volatile metabolites induced by fermentation. These metabolites were enriched in pathways related to flavonoid biosynthesis, alkaloid biosynthesis, aromatic amino acid metabolism, lipid metabolism, and carbon metabolism. Metagenomic analysis showed that Bacillus became the dominant genus on the tobacco leaf surface following inoculation with B. velezensis HJ-16, altering the microbial community composition, reducing diversity and evenness, and enhancing microbial metabolic activity. These findings underscore the potential of B. velezensis HJ-16 as a biotechnological tool to improve tobacco leaf quality.